Dasatinib increases endothelial permeability leading to pleural effusion. Issue 1 (18th January 2018) - Phan, Carole; Jutant, Etienne-Marie; Tu, Ly; Thuillet, Raphaël; Seferian, Andrei; Montani, David; Huertas, Alice; Bezu, Jan van; Breijer, Fabian; Noordegraaf, Anton Vonk; Humbert, Marc; Aman, Jurjan; et al.
Pleural effusion is a frequent side-effect of dasatinib, a second-generation tyrosine kinase inhibitor used in the treatment of chronic myelogenous leukaemia. However, the underlying mechanisms remain unknown. We hypothesised that dasatinib alters endothelial integrity, resulting in increased pulmonary vascular endothelial permeability and pleural effusion. To test this, we established the first animal model of dasatinib-related pleural effusion, by treating rats with a daily regimen of high doses of dasatinib (10 mg·kg −1 ·day −1 for 8 weeks). Pleural ultrasonography revealed that rats chronically treated with dasatinib developed pleural effusion after 5 weeks. Consistent with these in vivo observations, dasatinib led to a rapid and reversible increase in paracellular permeability of human pulmonary endothelial cell monolayers as reflected by increased macromolecule passage, loss of vascular endothelial cadherin and zonula occludens-1 from cell–cell junctions, and the development of actin stress fibres. These results were replicated using human umbilical vein endothelial cells and confirmed by decreased endothelial resistance. Interestingly, we demonstrated that this increased endothelial permeability is a reactive oxygen species (ROS)-dependent mechanism in vitro and in vivo using a cotreatment with an antioxidant agent, N -acetylcysteine. This study shows that dasatinib alters pulmonary endothelial permeability in a ROS-dependent manner in vitro and in vivo leading to pleural effusion. The drug dasatinib causes pleural effusion by disrupting the endothelial barrier with reactive oxygen species http://ow.ly/qOGE30gamGK